If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 + 13x = 42 + 6x Solving 35 + 13x = 42 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 35 + 13x + -6x = 42 + 6x + -6x Combine like terms: 13x + -6x = 7x 35 + 7x = 42 + 6x + -6x Combine like terms: 6x + -6x = 0 35 + 7x = 42 + 0 35 + 7x = 42 Add '-35' to each side of the equation. 35 + -35 + 7x = 42 + -35 Combine like terms: 35 + -35 = 0 0 + 7x = 42 + -35 7x = 42 + -35 Combine like terms: 42 + -35 = 7 7x = 7 Divide each side by '7'. x = 1 Simplifying x = 1
| 9x+10y=75 | | 12+12x=18+6x | | 4+7x=9x+2 | | 1+8x=8+7x | | 3x+21=14+10x | | 10+9x=30+4x | | 72+1x=10x+36 | | 4x+56=12x+16 | | 72+3x=12x+18 | | 27+5x=13x+18 | | 8+13x=5x+32 | | 2x+48=10x+24 | | 27+14x=5x+54 | | 2+9x=12+7x | | 72x+1=10x+36 | | 7x+30=5+12x | | 15+10x=25+5x | | 3+7x=6x+4 | | 1x+88=55+12x | | 2x+22=13x+11 | | 24+14x=56+6x | | 35+5x=10x+5 | | 35+2x=7x+10 | | 11x+15=8x+21 | | 36+7x=13x+24 | | 1x+40=16+9x | | 7x+36=13x+6 | | 20+8x=12x+4 | | 7x+30=1x+36 | | 40+11x=1x+70 | | 8x+8=7+9x | | 10+10x=14+8x |